The Role of the School Environment in the Formation of Student Character Values at SDN Gelaran 2 - Riski Rismala Sagita; Desty Dwi Rochmania (IJPSE : Indonesian Journal of Primary Science Education, 2022)
Character education in the current era is very much needed, because the Indonesian nation is experiencing a character crisis in the nation's children which results in the destruction of the Indonesian nation itself. In this case the school environment can be used as a means of building student character values. This research uses a case study qualitative approach. Data were collected using observation, interviews, and documentation methods. The purpose of this study is to describe the process and results of the formation of student character values ​​through the school environment at SDN Gelaran 2. The results of this study are (1) The formation of character values ​​for SDN Gelaran 2 students through the school environment is realized through habituation activities, examples, regulations made by teachers and schools, extracurricular activities, and also through the learning process in the classroom. The supporting and inhibiting factors in the process of forming student character values ​​through the school environment are the family environment, the community environment, and the children themselves (2) The results of the formation of student character values ​​through the school environment are very good. With the formation of student character values ​​through this school environment, students can behave well, be more polite and courteous to teachers and friends, students respect and respect each other more, students have a 5S culture (smile, greeting, greeting, polite, and courteous), and obey the rules. The polite behavior of students is shown by student attitudes such as greeting the teacher when passing by, respecting the teacher by walking behind him, saying excuse me when walking in front of the teacher, knocking on the door before entering the classroom, taking something with his right hand, looking down when the teacher is giving advice.